Age of Complementary Foods Introduction and Risk of Anemia in Children Aged 4-6 years: A Prospective Birth Cohort in China - F. Wang; Liu, H.; Wan, Y.; J. Li; Y. Chen; Zheng, J.; Huang, T.; D. Li (Sci RepSci RepSci Rep, 2017)
Age of complementary foods introduction is associated with childhood anemia, but the ideal age for the introduction of complementary foods to infants is a continuing topic of debate. We examined the longitudinal association between complementary foods introduction age and risk of anemia in 18,446 children from the Jiaxing Birth Cohort, who had detailed complementary feeding records at 3 and 6 months of age and had hemoglobin concentrations measured at 4-6 years. Early introduction of complementary foods at 3-6 months of age was significantly associated with a higher risk of anemia (odds ratio = 1.14; 95% confidence interval: 1.01-1.28) and a lower hemoglobin concentration of -0.84 g/L (95% confidence interval: -1.33 to -0.35) in children aged 4-6 years, compared with those fed complementary foods starting at 6 months of age. When it comes to the specific type of complementary foods, early introduction of all plant-based foods was associated with increased anemia risks and lower hemoglobin concentrations, while early introduction of most animal-based foods was not. These findings may be informative regarding the appropriate time to introduce complementary foods in infants.
Keywords: *Infant Nutritional Physiological Phenomena; Adult; Age Factors; Anemia/*epidemiology; Child; Child, Preschool; China/epidemiology; Female; Hemoglobins/metabolism; Humans; Infant; Male; Odds Ratio; Prospective Studies